CHARACTERISATION OF PRIMITIVE IDEALS OF TOEPLITZ ALGEBRAS OF QUOTIENTS - Rizky Rosjanuardi (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.2.112.67-71